2017
DOI: 10.1089/gtmb.2017.0108
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Next-Generation Sequencer for 24-Chromosome Aneuploidy Screening in Human Embryos

Abstract: This is the first study reporting preclinical validation and accuracy assessment of the Ion Torrent Personal Genome Machine (PGM) NGS-based comprehensive chromosome screening method using blastomeres and blastocysts. The NGS proved to be a robust methodology and is ready for clinical application in reproductive medicine, with the major advantage of low cost and enhanced precision when compared with other technologies used for comprehensive chromosome screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…They found that NGS specificity and sensitivity were both 100% and that there was more than 99% concordance between NGS and aCGH. These results were also confirmed by Zheng et al [30] using VeriSeq PGS kit (Illumina) with a smallest detection size of 1.8MB and Sachdeva et al [31] using Ion torrent Personal Genome Machine NGS. After the validation of NGS, its clinical applications in PGS cycles were also evaluated.…”
Section: Aneuploidysupporting
confidence: 64%
“…They found that NGS specificity and sensitivity were both 100% and that there was more than 99% concordance between NGS and aCGH. These results were also confirmed by Zheng et al [30] using VeriSeq PGS kit (Illumina) with a smallest detection size of 1.8MB and Sachdeva et al [31] using Ion torrent Personal Genome Machine NGS. After the validation of NGS, its clinical applications in PGS cycles were also evaluated.…”
Section: Aneuploidysupporting
confidence: 64%
“…However, in this study, only the good quality blastocysts were collected for TE biopsy and PGT-A, suggesting that the effect of embryo quality on euploid probability might be minimized. Notably, this study using hr-NGS for PGT-A differed from previous data using array comparative genomic hybridization analyses, which might be another reason for the different outcomes [ 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…By comparing the embryos obtained with previously established arrayCGH methodology, they confirmed that NGS has a 100% aneuploidy diagnosis consistency with arrayCGH. In addition to aneuploidy screening, Sachdeva et al reported the ability of NGS to detect segmental changes (as small as 14 Mb in size) [20], suggesting it could also be applied in the diagnosis of partial aneuploidy. Furthermore, by comparing NGS results with two other independent methodologies, namely qPCR-based comprehensive chromosome screening and Taqman allelic discrimination assays, Treff et al validated the use of NGS in PGD treatment for patients with monogenic disease [21].…”
Section: Discussionmentioning
confidence: 99%